The Consolidation Package and Its Impact on the Business Sector and Universities as Key Educational Institutions - Schlossberger, Otakar; Tomášková, Andrea (Publishing House of Wroclaw University of Economics and Business, 2024)
The Parliament of the Czech Republic has approved the Act on Consolidation of Public Budgets. The consolidation package introduced substantial changes on the expenditure and revenue side of the budget with the aim of stabilising public finances and reducing the government debt deficit. These measures will have an impact on the public sector, businesses and households, both internationally and regionally. The importance of universities as a key factor for the country’s economic development and competitiveness is emphasised.
Schlossberger, O. & Tomášková, A. (2024). The Consolidation Package and Its Impact on the Business Sector and Universities as Key Educational Institutions. In B. Drelich-Skulska, M. Sobocińska, & A. Tomášková (Eds.), The Importance of Universities for Society and Economy. The Experience of Researchers from the Visegrád Group (pp. 182-194). Publishing House of Wroclaw University of Economics and Business.
Keywords: Czechia; consolidation package; business sector; universities; public finances